Upaya Meningkatkan Penguasaan Mufrodat Melalui Media Gambar Pada Pembelajaran Bahasa Arab kelas VII-5 Semester I Madrasah Tsanawiyah Negeri 24 Jakarta Tahun Pelajaran 2015 /2016. - Esty Kusyanti (Jurnal Ilmiah Wahana Pendidikan, 2018)
The purpose of the research in writing this Classroom Action Research is to find out whether the use of picture media can improve Arabic learning outcomes (mastery mufrodat ) in students of class VII-5 MTs Negeri 24 Jakarta. The research method used isClass Action Researchin two cycles. Each cycle consists of four stages, namely the planning, implementation, observation and reflection stages. While data collection uses observation, tests, field notes and documentation that is directly carried out in the field. Sources of data from this study were students of class VII-5 MTs Negeri 24 Jakarta. Analysis of the data used includes presenting data, and drawing conclusions.learning Mufrodat Arabic using media Images of the subject matter الأدوات المدرسية have improved learning outcomes. This is indicated by student learning outcomes on the average value obtained by students in the final question cycle I / P1 is 68.57, the end of the I / P2 cycle is 73.33 then after doing the second cycle get an average value of 74 (Post Test 1) and value average 78.86 (Post Test 2). Based on the results of the study, it can be concluded thatlearning Mufrodat Arabicusing Media Visual Images can improve mufrodat mastery and learning outcomes of students of class VII-5 MTs Negeri 24 Jakarta Odd Semester 2015/2016 Academic Year.